Resilience, reflexivity, and decolonization: policy narratives in Kalaallit Nunaat - Jungsberg, Leneisja; Vestergård, Louise Ormstrup; Karlsdottir, Anna; Wardekker, Arjan (Frontiers in Climate, 2025)
BackgroundKalaallit Nunaat (Greenland) is undergoing rapid socio-economic and environmental transformations, particularly due to climate change, shifting governance structures and aspirations for political independence. These developments necessitate resilient policy approaches to support sustainable regional development while addressing historical and contemporary power dynamics.AimThis paper examines policy narratives in Kalaallit Nunaat, analyzing how they shape resilience building processes. Specifically, it explores the interplay between system oriented and community resilience approaches in national and regional policymaking.MethodA policy narrative analysis was conducted through a review of national strategies, government reports and other public policy documents from 2011 to 2020. The study applies a decolonial lens to examine how these narratives frame resilience, governance and development priorities in Kalaallit Nunaat.ResultsFour key narratives were identified: (1) the independence narrative, (2) the regional inequality narrative, addressing governance centralization and disparities between Nuuk and smaller settlements; (3) socio-economic and demographic challenges narrative, highlighting population decline, labour market issues and social inequalities; and (4) and climate change narrative, framing environmental shifts as both risks and economic opportunities. While all narratives prioritize independence, they differ in their perspectives on governance structure, local agency, and resilience building strategies. The study finds that policy narratives often assume resilience as an outcome of economic growth and political reforms, rather than a structured community driven process.ConclusionA decolonial approach to policy development in Kalaallit Nunaat requires centering community perspectives and strengthening locally driven decision-making processes. Rather than treating resilience as an assumed outcome of economic growth, policies should actively support long-term resilience-builidng by addressing structural inequalities, ensuring inclusive governance and integrating local knowledge into decision-making. By balancing community driven priorities with national governance reforms, policies can better support sustainable and equitable development.